Pengaruh Harga Dan Iklan Terhadap Keputusan Pembelian Makanan Cepat Saji Mc’Donalds Di Kota Malang - Wijaya, Aldo Naufal Surya; Wahono, Budi; Athia, Ita (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to determine the effect of Price and Advertising on Purchase Decisions of Mc.Donalds fast food in Malang City. The population used in this study were Malang City residents with the condition that they had purchased Mc products. Donalds or currently visiting Mc.Donalds fast food outlets at least once and domiciled in Malang. The data collection method in this study used questionnaires. The results of this study simultaneously indicate that price and advertising have a positive effect on purchasing decisions. Keywords: Price, Advertising, Purchase Decision